Fleksibilitas Kerja Dan OCB Islam Perspektif Terhadap Kinerja Karyawan: Kepuasan Kerja Sebagai Mediasi - Zaeniko Saputra; Ikhsan Maksum (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2024)
The study was conducted to explore the mediating role of job satisfaction on the effect of work flexibility and OCBIP on employee performance at PT Turen Indah Group. This research uses a quantitative approach method. The research data used are primary and secondary data. Data collection instruments are in the form of interviews and questionnaires. Samples were taken from a population of 153 employees. This research data analysis uses Structural Equation Modeling - Partial Least Square (SEM-PLS). The data analysis technique in this study uses Partial Least Square (PLS) with the help of Smart-PLS 4.1 software. The research findings show that work flexibility and OCBIP have a positive and significant effect on performance. In the mediating role, the results showed that job satisfaction was able to moderate the effect of OCBIP on performance. However, job satisfaction is not able to mediate the effect of work flexibility on performance. This research contributes to the human resource management literature covering work flexibility, OCBIP, employee performance, and mediating job satisfaction at PT Turen Indah Group.